Studi-studi tentang Al-Qur’an dalam Konteks Keindonesiaan menurut Pandangan Howard Federspiel - Farida, Nur Aini; Makbul, M (HAWARI : Jurnal Pendidikan Agama dan Keagamaan Islam, 2023)
The development of the interpretation of the Qur'an in Indonesia is certainly different from the developments in the Arab world. These differences are mainly due to differences in cultural and linguistic backgrounds. The interpretation of the Qur'an in Indonesia goes through a longer process when compared to that which applies in its place of origin. This study is a library research with historical approach. Howard analyzed one aspect of the scientific tradition of Indonesian Muslims, namely the study of the Qur'an as the main source of Islamic teachings. The Sunni Islamic tradition is important to Indonesian Muslim writers because it consistently draws on the sources of this tradition, namely the Qur'an, the Sunnah of the Prophet, and the works of scholars throughout Islamic history. Models of works on the exegesis of the Qur'an in Indonesia are basically derived from the works of Egyptian writers one hundred years ago.